Impact of the COVID-19 pandemic on behavioral changes in healthcare workers in Italy - Sansone, Vincenza; Miraglia del Giudice, Grazia; Della Polla, Giorgia; Angelillo, Italo Francesco; , The Collaborative Working Group; Faraone, Pasquale Di Girolamo; Mensorio, Mario Massimo; Muto, Mauro (Frontiers in Public Health, 2024)
Introduction: During the COVID-19 pandemic, adherence to wearing face mask and washing hands procedures, and achieving high COVID-19 vaccine coverage among healthcare workers (HCWs) were essential to minimize morbidity and possible death and to limit the transmission of the virus. The objectives of the cross-sectional survey were to explore the influence of COVID-19 on the use of preventive measures and vaccination willingness among HCWs in the Southern Italy and the associated factors. Methods: The survey was carried out from 15 June to 15 July 2023 among 521 HCWs in three randomly selected public hospitals. All data were collected through a self-administered questionnaire. Results: HCWs had a positive change in the use of preventive measures if they did not often/always use them before the pandemic but they are using in the current epidemiologic context and they were willing to use in a future epidemic situation. A positive change in the adherence to face mask-wearing was more likely among those with at least five years of university degree, nurses/midwives, and who had worked in COVID-19 wards. A positive change in alcohol-based hand rubbing was more likely in HCWs in Emergency/Critical/Infectious Diseases wards. HCWs who were more likely to believe that the COVID-19 vaccine should be mandatory for them had at least five years of university degree, in Emergency/Critical/Infectious Diseases wards, had received more than three doses of this vaccine, were more concerned to get infected during their activity, and had received information from scientific journals. HCWs more willing to receive the COVID-19 vaccine every year were males, physicians, in Emergency/Critical/Infectious Diseases wards compared to medical wards, had received more than three doses of this vaccine, believed that this vaccine should be mandatory for HCWs, and needed additional information. Discussion: The survey showed that the COVID-19 pandemic had an impact in the use of preventive measures among HCWs, not necessarily for the improvement or increase. Educational messages on the importance of these measures and regarding the promotion and recommendation of the vaccine need to be investigated and applied among HCWs in order to reduce vaccination gaps and the spread of the infection.